2010
DOI: 10.1021/ja101685u
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Catalysts for Dehydrogenation of Ammonia Borane with Preferential B−H Activation

Abstract: Cationic Pd(II) complexes catalyzed the dehydrogenation of ammonia borane in the most efficient manner with the release of 2.0 equiv of H2 in less than 60 s at 25 °C. Most of the hydrogen atoms were obtained from the boron atom of the ammonia borane. The first step of the dehydrogenation reaction was elaborated using density functional theory calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
126
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 176 publications
(128 citation statements)
references
References 39 publications
0
126
0
2
Order By: Relevance
“…Therefore, various hydrogen storage materials, that contain significant amounts of hydrogen, have been recently proposed. Boranes are probably one of the best known group among numerous hydrogen storage materials [4][5][6][7][8][9][10]. For example one can present ammonia borane (NH 3 BH 3 ) [4][5][6][7][8][9][10]-the attractiveness of this material stems from its high stability, even at higher temperature (the melting point is 104˝C), as well as its large hydrogen storage capacity (19.6 wt% H 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, various hydrogen storage materials, that contain significant amounts of hydrogen, have been recently proposed. Boranes are probably one of the best known group among numerous hydrogen storage materials [4][5][6][7][8][9][10]. For example one can present ammonia borane (NH 3 BH 3 ) [4][5][6][7][8][9][10]-the attractiveness of this material stems from its high stability, even at higher temperature (the melting point is 104˝C), as well as its large hydrogen storage capacity (19.6 wt% H 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Boranes are probably one of the best known group among numerous hydrogen storage materials [4][5][6][7][8][9][10]. For example one can present ammonia borane (NH 3 BH 3 ) [4][5][6][7][8][9][10]-the attractiveness of this material stems from its high stability, even at higher temperature (the melting point is 104˝C), as well as its large hydrogen storage capacity (19.6 wt% H 2 ). It has been demonstrated that the former feature of ammonia borane crystal originates predominantly from the existence of polar dihydrogen bonds N-H δ`¨¨¨´δ H-B between monomers [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Group 10 transition metal complexes also have been exploited to achieve this target: only a few results are represented by the Ni 0 -Enders' NHC (1,3,4-triphenyl-4,5-dihydro-1H-1,2,4-triazol- 19 However, in comparison with the rapidly growing number of catalysts, † Electronic supplementary information (ESI) available: (S1 and S2) X-ray photoelectron spectroscopy (XPS) and IR spectra of the spent fuel. the amount of experimental studies that deal with mechanistic details is still limited.…”
mentioning
confidence: 99%
“…19 In addition to imparting the efficient dehydrogenation ability of 1, we discovered that the dehydropolymerization forms mostly B-B bonds in a less regular process with the preferential activation of B-H bonds, but did not further investigate the structural elucidation of the spent fuel for mechanism analysis in a recent preliminary communication. 19 We initially thought that the composition of the dehydropolymerized product could be similar to other reported AB spent fuels (2) was performed. As compared to the palladium catalyst, the nickel catalyst (2) was less active in AB dehydrogenation releasing only 1.8 equiv.…”
mentioning
confidence: 99%